MARHAENISM: SOCIAL IDEOLOGY CREATE BY SUKARNO - Kuswono Kuswono (Historia: Jurnal Pendidikan Sejarah FKIP UM Metro, 2016)
This paper describes an understanding born in the occupied country, namely Indonesia (Dutch East Indies) to oppose colonialism, capitalism and imperialism in the early twentieth century. Marhaenisme, Sukarno call that ideology. The purpose of this paper is to provide an understanding of the political ideology that developed early days of the movement of the twentieth century. Until now Marhaenism still interesting to be studied and understood even applied in the life of the nation. Writings using the historical method is descriptive-analysis. Sources of data obtained from the literature, library materials, and writings by Sukarno as the originator of this ideology. Marhaenism an ideology of opposition against colonialism and foreign imperialism. With the spirit of Sukarno hoped Marhaen colonized people will soon emerge from the downturn. Then able to process, enjoy the fruits of his labors without having to submit to someone else. Marhaenism not just a symbol of resurrection of the wong cilik but a spirit of all the people of Indonesia that is free from physical and mental colonization coming from the outside.